2017
DOI: 10.1001/jamainternmed.2017.0197
|View full text |Cite|
|
Sign up to set email alerts
|

Association of Intensive Blood Pressure Control and Kidney Disease Progression in Nondiabetic Patients With Chronic Kidney Disease

Abstract: IMPORTANCE The optimal blood pressure (BP) target remains debated in nondiabetic patients with chronic kidney disease (CKD). OBJECTIVE To compare intensive BP control (<130/80 mm Hg) with standard BP control (<140/90 mm Hg) on major renal outcomes in patients with CKD without diabetes. DATA SOURCES Searches of PubMed, MEDLINE, Embase, and Cochrane Library for publications up to March 24, 2016. STUDY SELECTION Randomized clinical trials that compared an intensive vs a standard BP target in nondiabetic adults wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
81
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 124 publications
(90 citation statements)
references
References 43 publications
0
81
0
9
Order By: Relevance
“…Additionally, in patients without CKD, a dose-response relationship was observed in which a greater reduction in mean arterial pressure associated with greater eGFR decline, and the balance between cardiovascular benefits and kidney risks were less favorable with larger blood pressure reductions [14]. A systematic review of 9 clinical trials conducted in participants with non-diabetic CKD demonstrated that compared to standard treatment, intensive blood pressure treatment did not reduce rates of overall eGFR decline, reaching 50% eGFR decline, or serum creatinine doubling [20]. In the Action to Control Cardiovascular Risk in Diabetes trial of patients with type 2 diabetes randomized to a target systolic blood pressure of < 120 versus < 140 mm Hg, eGFR was lower and risk of reaching eGFR < 30 mL/min/1.73 m 2 was higher without benefit on cardiovascular outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in patients without CKD, a dose-response relationship was observed in which a greater reduction in mean arterial pressure associated with greater eGFR decline, and the balance between cardiovascular benefits and kidney risks were less favorable with larger blood pressure reductions [14]. A systematic review of 9 clinical trials conducted in participants with non-diabetic CKD demonstrated that compared to standard treatment, intensive blood pressure treatment did not reduce rates of overall eGFR decline, reaching 50% eGFR decline, or serum creatinine doubling [20]. In the Action to Control Cardiovascular Risk in Diabetes trial of patients with type 2 diabetes randomized to a target systolic blood pressure of < 120 versus < 140 mm Hg, eGFR was lower and risk of reaching eGFR < 30 mL/min/1.73 m 2 was higher without benefit on cardiovascular outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…A previous meta-analysis based on 9 investigations in chronic kidney disease patients found that IBP control did not provide additional benefits for renal outcomes when compared with standard BP control during the follow-up period of 3.3 years, whereas this effect was not observed in diabetic patients [43]. However, the authors did not investigate the treatment effects of IBP control on cardiovascular outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Although a target of <130/80 mmHg has been recommended for individuals with diabetes or micro‐ or macroalbuminuria, the appropriateness of a BP target lower than <140/90 in diabetic patients is the subject of debate . There is also uncertainty about the appropriateness of a BP target lower than <140/90 in patients with CKD . A third of diabetic participants with HbA1c levels above the target and under‐utilisation of antiplatelet therapies in participants with vascular disease and anticoagulant therapy in participants with AF also demonstrate therapeutic inertia.…”
Section: Discussionmentioning
confidence: 99%